Porous Se@SiO2 nanospheres alleviate diabetic retinopathy by inhibiting excess lipid peroxidation and inflammation - Tian Niu; Xin Shi; Xijian Liu; Haiyan Wang; Kun Liu; Yupeng Xu (BMC, 2024)
Abstract Background Lipid peroxidation is a characteristic metabolic manifestation of diabetic retinopathy (DR) that causes inflammation, eventually leading to severe retinal vascular abnormalities. Selenium (Se) can directly or indirectly scavenge intracellular free radicals. Due to the narrow distinction between Se's effective and toxic doses, porous Se@SiO2 nanospheres have been developed to control the release of Se. They exert strong antioxidant and anti-inflammatory effects. Methods The effect of anti-lipid peroxidation and anti-inflammatory effects of porous Se@SiO2 nanospheres on diabetic mice were assessed by detecting the level of Malondialdehyde (MDA), glutathione peroxidase 4 (GPX4), decreased reduced/oxidized glutathione (GSH/GSSG) ratio, tumor necrosis factor (TNF)-α, interferon (IFN)-γ, and interleukin (IL) -1β of the retina. To further examine the protective effect of porous Se@SiO2 nanospheres on the retinal vasculopathy of diabetic mice, retinal acellular capillary, the expression of tight junction proteins, and blood-retinal barrier destruction was observed. Finally, we validated the GPX4 as the target of porous Se@SiO2 nanospheres via decreased expression of GPX4 and detected the level of MDA, GSH/GSSG, TNF-α, IFN-γ, IL -1β, wound healing assay, and tube formation in high glucose (HG) cultured Human retinal microvascular endothelial cells (HRMECs). Results The porous Se@SiO2 nanospheres reduced the level of MDA, TNF-α, IFN-γ, and IL -1β, while increasing the level of GPX4 and GSH/GSSG in diabetic mice. Therefore, porous Se@SiO2 nanospheres reduced the number of retinal acellular capillaries, depletion of tight junction proteins, and vascular leakage in diabetic mice. Further, we identified GPX4 as the target of porous Se@SiO2 nanospheres as GPX4 inhibition reduced the repression effect of anti-lipid peroxidation, anti-inflammatory, and protective effects of endothelial cell dysfunction of porous Se@SiO2 nanospheres in HG-cultured HRMECs. Conclusion Porous Se@SiO2 nanospheres effectively attenuated retinal vasculopathy in diabetic mice via inhibiting excess lipid peroxidation and inflammation by target GPX4, suggesting their potential as therapeutic agents for DR.